2014
DOI: 10.1002/poc.3350
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil solutions: NMR study of acid-base equilibrium in water and DMSO

Abstract: A comprehensive analysis of solutions of 5‐fluorouracil (5FU) in water and an organic medium (dimethylsulfoxide, DMSO) was carried out using quantum chemical methods and nuclear magnetic resonance (NMR) spectroscopy. The details of anionic form generation in the solution of 5FU with an equimolar amount of potassium hydroxide were studied by 13С, 1Н, 15N and 19F NMR. Interpretation of NMR spectral data was carried out using quantum chemical calculations at the TPSSTPSS/6‐311+G(d,p) level of theory. Specific sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…This is in line with the recent NMR study on 5-FU and its N 1 -analogues. [16] However, according to NMR analysis of the reaction mixture (the small inset in Figure 3) we are confident that the regioselectivity in the reaction between 5-FU and FcCOCl follows the same pattern as that described for uracil and thymine.…”
Section: Nmr Analysis Of the Reaction Mixturementioning
confidence: 78%
“…This is in line with the recent NMR study on 5-FU and its N 1 -analogues. [16] However, according to NMR analysis of the reaction mixture (the small inset in Figure 3) we are confident that the regioselectivity in the reaction between 5-FU and FcCOCl follows the same pattern as that described for uracil and thymine.…”
Section: Nmr Analysis Of the Reaction Mixturementioning
confidence: 78%
“…This result is supported by the reaction field calculations with the isodensity polarizable continuum (IPC) model, with the equilibrium constant ratio, K eq (N1) / K eq (N3) = 5 × 10 4 . In the case of 5F U , the N1 – / N3 – anion fraction ratio in aqueous alkaline solution was found to be 0.61 [ 60 ]. The N3 – anion, if formed in aqueous solution, in the gas phase can isomerize to N1 – in the presence of neutral nucleobase [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The N3 – anion, if formed in aqueous solution, in the gas phase can isomerize to N1 – in the presence of neutral nucleobase [ 20 ]. According to the in vacuo ab initio calculations, the N1 – anion of [ U -H] – is more stable than N3 – by 58.5 kJ/mol [ 59 ]; for [5F U -H] – this difference is 49.9 kJ/mol [ 60 ]. The energy barrier (185.4 kJ/mol) calculated [ 61 ] for the uracil N1 – —> N3 – conversion is too high to be overcome at thermal energies in our instrument.…”
Section: Resultsmentioning
confidence: 99%
“…However, the measurement of acidity is sometimes very difficult, especially when dealing with a mixture of isomers that are difficult to separate, for example, highly labile tautomeric forms. Additionally, different schemes are known for the theoretical estimation of the p K a vlues of uracils . Such a diversity of works is due to the ongoing development of computational methods of quantum chemistry, providing novel opportunities for more accurate assessment of p K a .…”
Section: Introductionmentioning
confidence: 99%
“…Abdrakhimova and co‐authors carried out a comprehensive analysis of solutions of halouracils in water and organic media Dimethylsulfoxide (DMSO) in a number of works using quantum chemical methods and Nuclear magnetic resonance (NMR) spectroscopy. They found that in an alkaline medium in DMSO, for fluorouracil, an anion with deprotonation in the N1 position of the pyrimidine ring was formed, whereas in water and in an alkaline solution it was a mixture of two anions with deprotonation on N1 and N3 positions with a predominant content of the latter.…”
Section: Introductionmentioning
confidence: 99%